2017
DOI: 10.15603/1982-8756/roc.v13n26p311-338
|View full text |Cite
|
Sign up to set email alerts
|

Influência da Governança Corporativa na Evidenciação Voluntária de Informações de Natureza Socioambiental

Abstract: O objetivo do estudo é analisar a influência da governança corporativa na evidenciação voluntária de natureza socioambiental em empresas familiares e não familiares listadas na BM&FBovespa. A pesquisa é natureza descritiva, documental e quantitativa, realizada com uma amostra de 64 empresas que divulgaram o relatório de sustentabilidade no modelo GRI 2014. A evidenciação socioambiental voluntária foi analisada por meio de um constructo composto por 150 indicadores das dimensões econômica, ambiental e socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
1
1
3
Order By: Relevance
“…This finding converges with the study by Correa et al (2017) who analyzed the environmental disclosure of 34 American publicly traded companies traded on the New York Stock Exchange (NYSE) and found that the ROA was negatively related to the disclosure of social and environmental information. Divergent from the finding of Mazzioni, Cofsevicz, Moura, Macêdo and Krüger (2017) in which, for the variable profitability were noticed positive and significant coefficients in relation to the socio-environmental disclosure of the companies, indicating that more profitable companies are more prone and committed with socio-environmental responsibility.…”
Section: Multivariate Analysiscontrasting
confidence: 83%
See 1 more Smart Citation
“…This finding converges with the study by Correa et al (2017) who analyzed the environmental disclosure of 34 American publicly traded companies traded on the New York Stock Exchange (NYSE) and found that the ROA was negatively related to the disclosure of social and environmental information. Divergent from the finding of Mazzioni, Cofsevicz, Moura, Macêdo and Krüger (2017) in which, for the variable profitability were noticed positive and significant coefficients in relation to the socio-environmental disclosure of the companies, indicating that more profitable companies are more prone and committed with socio-environmental responsibility.…”
Section: Multivariate Analysiscontrasting
confidence: 83%
“…The justification for the non-influence of political connections on the level of socioenvironmental evidence in this study may consist in the fact that Brazil is characterized as a code law country, with a developing stock market and relatively weak institutional environment (Mazzioni et al, 2017). This inference was verified in Zhang's study (2017), in which it was noticed that the positive effect of political connections on the disclosure of information of corporate environmental responsibility is more likely to occur in environments marked by strict rules and regulations that ensure the direction of the behavior of companies in this sense, that is, in environments where institutional development is strong.…”
Section: Discussion Of Resultsmentioning
confidence: 98%
“…Consequentemente, as companhias remodelaram sua estrutura de capital, devido ao crescimento muito intenso de suas atividades. Nesse novo cenário, surgiram muitos debates sobre o tema governança corporativa no tocante a dispersão do capital, ou seja, a separação entre a propriedade e a gestão da empresa (Mazzioni, Cofsevicz, Moura, Macêdo, & Kruger, 2017), e também a divergência entre os interesses dos sócios e gestores (Mac Lennan, Semensato, & Oliva, 2014), propiciando um confl ito de agência.…”
Section: Teoria Dos Stakeholdersunclassified
“…Segundo Moura, Almeida e Vecchia (2017), a efi cácia de um conselho administrativo é caracterizada por apresentar participação expressiva de diretores independentes externos à companhia e que um conselho é caracterizado de baixa qualidade quando é constituído, em sua grande maioria, por membros internos ou, então, por diretores externos que tenham alguma relação com controladores e gestores e presidido pelo diretor-presidente da companhia. Pois, diferentes de membros interno e externos, um conselho com membros independes exercem melhor o monitoramento e controle dos gestores oportunistas (Alves, 2014), e são menos arriscados de problemas com membros de auto interesse e que possam ser infl uenciados por controladores e gestores (Moura et al, 2017).…”
Section: Teoria Dos Stakeholdersunclassified
“…Ademais, arma-se que o ambiente institucional introduz barreiras ao pleno desenvolvimento do mercado de ações brasileiro e isso pode explicar o impacto negativo das práticas de governança corporativa sobre o nível de evidenciação dos custos ambientais (Mazzioni, Cofsevicz, Moura, Macêdo & Kruger, 2017).…”
Section: Tabelaunclassified